Dinâmica de trabalho em equipes interfuncionais : um estudo de caso em uma empresa de serviços - Oliveira, Eider Arantes de (2014)
A function, previously restricted to a specific department inside the organizational structure focusing in to accomplish a job, now a days must be inserted into a process that shares activities, knowledge and skills with other organizational functions. Therefore, arises the concept of functional integration that starts from the need to make easier the coordination and synchronization of the relationships between different organizational functions to accomplish a common objective. One of several factors identified in the literature that make up and characterize this concept is the cross functional team, a group of professionals with diverse academic and experienced background coming from distinct functions, grouped in a permanent or temporary basis and under one leader to accomplish a specific task. Several studies in the literature address the subject and highlights the components of a cross-functional team, mostly on quantitative approaches. Therefore, the objective of this study is based on the theoretical gap concerning the characterization of the internal working dynamics in a cross-functional team applied in the contexts of strategy development, product development, portfolio management, sales channels management and business analysis in a Brazilian organization delivering services. Part of the process to achieve the objective, four categories and nineteen subcategories of analysis have been identified based on the literature, as well as the impact on the internal dynamics, team performance and organization: 1. Constitution of the functional team; 2. Task drivers; 3. Behaviors and Attitudes of the Group; 4. Environmental Factors. Based on In-depth interviews, observation and documental research on a single case study, it was possible to analyze the process of how a group acts and reacts to the influences and change circumstances from the perspective of the identified elements. The results can help managers to mitigate risks of failures and to identify improvement opportunities when working with cross-functional teams. Therefore, they can increase the chances of conducting more collaborative processes and avoiding conflicts within cross-functional teams and between the participating functions, reaching a superior organizational performance.